A high ratio of IL-12Rβ2-positive tumor-infiltrating lymphocytes indicates favorable prognosis in laryngeal cancer. (November 2017) - Tao, Ye; Gross, Neil; Liu, Yehai; Zhang, Liyong; Li, Guojun; Huang, Zhigang; Yang, Jianming
Highlights: IL-12Rβ2 interact with TILs to affect immune equilibrium and immunoediting in LC. Laryngeal IL-12Rβ2 + TILs differed by the locations and differentiation in LC. Ratio of IL-12Rβ2 + TILs ≥35% significantly predicts favorable survival in LC. Ratio of IL-12Rβ2 + TILs ≥35% has potential implications of treatment modalities for LC. Abstract: Background: The purpose of this study was to elucidate IL-12Rβ2's roles as a tumor-associated immunological molecule, delineate the complex roles of IL-12Rβ2 + tumor-infiltrating lymphocytes (TILs) and tumor cell IL-12Rβ2 expression in the tumor microenvironment, and determine the correlation of IL-12Rβ2 + TILs and tumor cell IL-12Rβ2 expression with clinical prognosis. Methods: We assessed mRNA and protein levels in matched laryngeal cancer tissues (LTs) and adjacent normal mucous membrane tissues (ANMMTs) from 3 laryngeal cancer (LC) patients and ratios of IL-12Rβ2 + TILs in matched LTs and ANMMTs from 61 LC patients. We used the Kaplan-Meier log-rank test and Cox regression hazard ratios to analyze survival. Results: Comparative proteomic and transcriptomic assays revealed that matched LTs and ANMMTs from the 3 patients had significantly different IL-12Rβ2 and IFN-γ expression; the ratio of IL-12Rβ2 + TILs decreased with lower degrees of tumor differentiation. Among all 61 LC patients, the IL-12Rβ2 + TIL ratio in ANMMTs (38.5% ± 22.8%) was significantly higher than that in LTs (29.7% ± 19%; p < .001). Kaplan-Meier analysis revealed that patients with an IL-12Rβ2 + TIL ratio ≥35% had significantly better survival than those with an IL-12Rβ2 + TIL ratio <35% (log rank p = 0.041). Multivariable analysis showed a significant association between a high IL-12Rβ2 + TIL ratio and overall survival (hazard ratio, 0.14; 95% confidence interval, 0.03–0.77). Conclusion: Tumor cell differentiation is associated with TILs' expression of IL-12Rβ2, and an IL-12Rβ2 + TIL ratio ≥35%) indicates favorable prognosis in LC.